Adult Learning Principles and Peer Delivery Improve Satisfaction of Electronic Medical Record Onboarding Education - Lawrence, Joanna; Tanny, Sharman Tan; Heaton, Victoria; Andrew, Lauren (ACI Open, 2020)
Objectives Given the importance of onboarding education in ensuring the safety and efficiency of medical users in the electronic medical record (EMR), we re-designed our EMR curriculum to incorporate adult learning principles, informed and delivered by peers. We aimed to evaluate the impact of these changes based on their satisfaction with the training.Methods A single site pre- and post-observational study measured satisfaction scores (four questions) from junior doctors attending EMR onboarding education in 2018 (pre-implementation) compared with 2019 (post-implementation). An additional four questions were asked in the post-implementation survey. All questions employed a Likert scale (1–5) with an opportunity for free-text. Raw data were used to calculate averages, standard deviations and the student t-test was used to compare the two cohorts where applicable.Results There were a total of 98 respondents in 2018 (pre-implementation) and 119 in 2019 (post-implementation). Satisfaction increased from 3.8/5 to 4.5/5 (p < 0.0001) following implementation of a peer-delivered curriculum in line with adult learning practices. The highest-rated factors were being taught by other doctors (4.9/5) and doctors having the appropriate knowledge to deliver training (4.9/5). Ninety-two percent of junior doctors were motivated to engage in further EMR education and 90% felt classroom support was adequate.Conclusion EMR onboarding education for medical users is a critical ingredient to organizational safety and efficiency. An improvement in satisfaction ratings by junior doctors was demonstrated after significant re-design of the curriculum was informed and delivered by peers, in line with adult learning principles.
Keywords: electronic medical record; adult learning principles; user satisfaction